Primary Extranodal, Extralymphatic Hodgkin Lymphoma of the Mandible - Guido Ricardo Gonzalez-Fontal; Joaquin D. Rosales; Roberto Jaramillo; Andres F. Henao-Martinez (Case Reports in Medicine)
Primary extranodal, extralymphatic Hodgkin lymphomas (PEEHLs) are a rare occurrence. When they are encountered, they become diagnostic challenges. We are describing the uniqueness of a case of PEEHL affecting the mandible with his early response to the available chemotherapy.